Reinterpreting Experiential Learning for FSL in Canada: Bridging Community and Classroom - Barysevich, Alena; Lebel, Marie-Élaine (Nouvelle Revue Synergies Canada, 2025)
This article presents a reinterpreted approach to experiential learning (EL) for French as a Second Language (FSL) in Canada, where asymmetrical bilingualism, minority Francophone settings, and widespread multilingualism profoundly shape learner experience. Rather than viewing these sociolinguistic realities as obstacles, the article argues that they can be leveraged for creating meaningful, contextually grounded experiential learning experiences.The presented approach consists of two complementary components: community-based EL and classroom-based EL, the Discussion Group and Peer Review Summary (DGPRS). Both components are grounded in Kolb’s experiential learning cycle and framed through task-based and genre-based pedagogies. Community-based EL systematically integrates authentic interactions with Francophone communities—whether local, institutional, or digital—directly into the FSL curriculum, thereby expanding learners’ exposure to linguistic diversity and enhancing social value of French. The DGPRS, as a form of classroom-based EL, creates structured opportunities for authentic communication, peer observation, collaborative reflection, and the development of a classroom-based language community, that validates learners as legitimate users of French. Together, these two complementary components foster experiential learning that enhances sociolinguistic competence and learners’ ability to navigate linguistic diversity. This EL approach bridges classroom learning and real-world experience.